New-onset ascites as a manifestation of virologic relapse in patients with hepatitis C cirrhosis - Chua DL (Dove Medical Press, 2014)
Deborah Lim Chua, Thomas Hahambis, Samuel H SigalDivision of Gastroenterology, Department of Medicine, New York University School of Medicine, New York, NY, USABackground: Chronic hepatitis C is the most common cause of cirrhosis in industrialized countries. Successful treatment of chronic hepatitis C in patients with advanced fibrosis or cirrhosis has significant benefits, including improvements in inflammation, fibrosis, and portal hypertension, with prevention of esophageal varices and clinical decompensation.Case: In this report, we present two patients with well-compensated hepatitis C cirrhosis who achieved an end-of-treatment response on a direct-acting antiviral therapy-based triple regimen for hepatitis C virus, but subsequently presented with new-onset ascites associated with virologic relapse.Conclusion: We propose that the development of ascites in this setting is due to the adverse impact of inflammation of the virologic relapse on portal hypertension. Our observation that ascites formation can be a manifestation of virologic relapse has potentially important clinical implications, as it highlights not only the importance of close monitoring of cirrhotic patients after achieving end-of-treatment response but also the impact of active inflammation on the severity of portal hypertension.Keywords: chronic hepatitis C, cirrhosis, virologic relapse, portal hypertension, ascites